FAKTOR KEPERILAKUAN ORGANISASI TERHADAP KEGUNAAN SISTEM AKUNTANSI KEUANGAN DAERAH DENGAN KONFLIK KOGNITIF DAN KONFLIK AFEKTIF SEBAGAI INTERVENING (Fokus Ekonomi, 2011)
The purpose of this study was to determine the effect of organizational behavioral factors,cognitive and affective conflict against SAKD usefulness and behavioral factors influence theorganization of cognitive and affective conflict and behavioral factors influence the organizationof the usefulness SAKD inervening by the presence of cognitive and affective conflict. Study'srespondents were civil servants who work on DPPKAD Local Government of Magelang regency.This study sample is determined by using purposive sampling, in order to obtain a sample of 114respondents with a return rate of 76%. The hypothesis in this study were tested using multipleregression approach.The results showed that only the use of information technology and cognitiveconflict has a positive effect on usability SAKD. Training and clarity of purpose has a positiveeffect on cognitive conflict. Clarity of purpose,superior support,and information tecnologynegatively affect affective conflict and training proved negative effect to affective conflict.Cognitive conflict SAKD positive effect on usability, but not with affective conflict. Cognitiveconflict as a variable interverning between behavior organizational factors with usability SAKD,suggesting that behavior organizational factors have a positive relationship to the usability SAKD,mediated by cognitive conflict. Interverning affective conflict as a variable between organizationalfactors with usability SAKD, there is a negative relationship .Key words: organizational behaviour factor, conflict cognitive, affective conflict ,financialaccounting system.